Superconducting gap and pseudogap - Guy Deutscher (Физика низких температур, 2006)
The discovery of the pseudogap has been a fundamental advance in uncovering the new physics
of the high-Tc cuprates. Yet, its meaning is still far from being clear. In particular, its relation to
the superconducting gap remains an object of controversy. While many authors consider that it is a
high temperature precursor of superconductivity, which turns into the superconducting gap at low
temperatures, others contend that it is a normal state property related only indirectly to
superconductivity. We review a number of experiments such as single particle tunneling, Andreev–Saint–James
reflections and others, and conclude that in the underdoped regime there exists
considerable evidence for the existence of two distinct energy scales, the superconducting gap and
the pseudogap, which appear to merge into one another in overdoped samples.